2014
DOI: 10.1177/0265659013519258
|View full text |Cite
|
Sign up to set email alerts
|

‘Happy and excited’: Perceptions of using digital technology and social media by young people who use augmentative and alternative communication

Abstract: Young people are using digital technology and online social media within their everyday lives to enrich their social relationships. The UK government believes that using digital technology can improve social inclusion. One well-recognized outcome measure for establishing social inclusion is to examine opportunities for self-determination. Individuals with physical disabilities and complex communication needs who use forms of augmentative and alternative communication (AAC) have lower social participation oppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 45 publications
1
42
0
Order By: Relevance
“…Specifi cally, researchers have observed that individuals who use AAC face a range of barriers as they learn to navigate online communities (Hynan et al, 2014;Raghavendra et al, 2013). These barriers may result from both intrinsic and extrinsic factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifi cally, researchers have observed that individuals who use AAC face a range of barriers as they learn to navigate online communities (Hynan et al, 2014;Raghavendra et al, 2013). These barriers may result from both intrinsic and extrinsic factors.…”
Section: Discussionmentioning
confidence: 99%
“…These barriers may result from both intrinsic and extrinsic factors. Prior research suggests that the most commonly identifi ed barriers for adolescents and young adults with complex communication needs learning to use social media are the lack of well-developed literacy skills and technology supports (Hynan et al, 2014;Raghavendra et al, 2012). In contrast, the older participants in the present study all had well-developed language and literacy skills; they primarily highlighted intrinsic and extrinsic barriers related to access diffi culties (e.g., limited motor skills), their slow rate during online synchronous communication (e.g., interactions via Google Talk 21 ), and technology limitations (e.g., problems with their AAC devices, poorly designed display layouts, limited accessibility of social media sites, and diffi culties connecting their AAC devices with social media sites).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study also found that online activities were similar for both groups, yet parents of the teens with a disability were more concerned about Internet safety (Lathouwers et al, ). However, a British study of 25 adolescents and young people with communication disabilities found that Internet and social media use were limited more by literacy skills and the availability of AT (Hynan et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The benefits of being online were perceived by the participants as: increased opportunities for self-determination and self-representation; increased online social capital opportunities; talking to everyone; reduced isolation; possible dating support and tools with which to build resilience networks [102,103]. These findings may have implications for future research to consider whether being online can support perceptions of social inclusion and participation for people who use AAC, in much the same way as previously discussed antecedents support perceptions of community-based social inclusion and social belonging in the offline world.…”
Section: Resultsmentioning
confidence: 99%